Stability of Freeze-Dried Sera Stored at Different Temperatures for the Detection of Anti-Leishmania infantum Antibodies Using Direct Agglutination Test. - Zahra Kakooei; Mehdi Mohebali; Behnaz Akhoundi; Abbas Rahimi Foroshani (Tehran University of Medical Sciences, 2014)
This study aimed to evaluate freeze-dried sera as an alternative to non-freeze dried for detection of anti-Leishmania infantum antibodies over the course of 11 months using the direct agglutination test (DAT).Altogether, 60 serum samples (30 from humans and 30 from dogs) were collected from various geographical locations in Iran. All the collected sera were pooled and each pooled serum sample contained 10 different sera. In the beginning, the human and dog pooled sera were categorized as positive (weak and strong) and negative based on anti-L. infantum antibodies using the DAT. All the freeze-dried and non-freeze-dried sera were stored at -70°C, -20°C, 4°C, 22-28°C and 56°C for 11 months. The positive and negative human and dog pooled sera were separately tested using the DAT each month and the results were compared to non-freeze-dried sera kept under the same conditions.We found strong agreement (100%) between the results obtained from freeze-dried human and dog in strong DAT positive sera kept at -70°C, -20°C, 4°C and 22-28°C during this study. The human and dog pooled sera stored at 56°C were corrupted after 2 weeks. The DAT results were highly reproducible using freeze-dried human pooled sera in the beginning and month 11 of this study (CV = 0.036).Freeze-dried human and dog strong DAT positive sera are highly stable under different temperature conditions, are easy to transport and are safe for use as positive and negative serum controls in laboratories.